UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK UMBI LOBAK PUTIH (Raphanus sativus L) TERHADAP PERTUMBUHAN BAKTERI Propionibacterium acnes DAN Staphylococcus epidermidis - Wiwid Deswita; kartika manalu; Efrida Pima Sari Tambunan (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the ability of white radish tuber extract (Raphanus sativus L) in inhibiting the growth of bacteria Staphylococcus epidermidis and Propionibacterium acnes and to determine the effective concentration of white radish tuber extract (Raphanus sativus L) in inhibiting the growth of Propionibacterium acnes and Staphylococcus epidermidis. Based on the results of tests using Analysis of Variance SPSS 21 (ANOVA) showed that there was an effect of antibacterial effectiveness on Staphylococcus epidermidis and Propionibacterium acnes with a significance value (α <0.05). The 100% extract concentration in bacteria Propionibacterium acnes is the best concentration in forming the inhibition zone with a diameter of 15.6 mm and the 100% extract concentration in the bacteria Staphylococcus epidermidis is the best concentration in forming the inhibition zone with a diameter of 13.3 mm.